Preventive effect of Juniperus procera extract on liver injury induced by lithocholic acid - Alkhedaide, Adel Qlayel (Cellular and Molecular Biology, 2018)
Bile acids are strong cytotoxic endogenous compounds implicated in several diseases in various organs, such as the liver, gallbladder and small and large intestines. Lithocholic acid is one such acid, produced by flora, and causes liver injury, cholestasis, and colon cancer. The present study aimed to examine the preventive effects of Juniperus procera extract on lithocholic acid"‘induced liver injury in experimental mice. Forty adult male mice were divided equally into four groups. The negative control group gained free access to food and water. The second group was orally treated with 150 mg/kg of Juniperus procera extract alone, the third group was treated with 1% lithocholic acid alone and the fourth group was co-treated with 150 mg/kg of Juniperus procera extract and 1% lithocholic acid. Blood and hepatic tissues were collected and assayed for biochemical, molecular and histopathological changes. Lithocholic acid toxicity shows a significant increase in the serum levels of the liver function parameters, which were prevented via the Juniperus procera co-administration. Furthermore, lithocholic acid significantly downregulates the mRNA expression of ABCG8, OATP2, SULT2A, CAR, FXR, CYP2B10, MRP2 and UGT1A, and Juniperus procera prevented this effect. Histopathological investigations of the hepatic tissues showed that lithocholic acid exhibited severe hepatotoxicity, with areas of irregularly distributed necrosis with inflammatory infiltration. Juniperus procera co-treated group showed a slight change in the hepatic tissue, diminished necrotic areas, and inflammatory infiltration. In conclusion, this study clarified the preventive effect of Juniperus procera extract administration on hepatotoxicity induced by lithocholic acid exposure in experimental mice.